Dementia prevention, intervention, and care: 2020 report of the Lancet Commission - Livingston, Gill; Huntley, Jonathan; Sommerlad, Andrew; Ames, David; Ballard, Clive; Banerjee, Sube; Brayne, Carol; Burns, Alistair; Cohen-Mansfield, Jiska; Cooper, Claudia; Costafreda, Sergi G; Dias, Amit; et al. (The Lancet (British edition), 2020)
Using hearing aids appears to reduce the excess risk from hearing loss. New evidence supports adding three modifiable risk factors—excessive alcohol consumption, head injury, and air pollution—to our 2017 Lancet Commission on dementia prevention, intervention, and care life-course model of nine factors (less education, hypertension, hearing impairment, smoking, obesity, depression, physical inactivity, diabetes, and infrequent social contact). Encourage use of hearing aids for hearing loss and reduce hearing loss by protection of ears from excessive noise exposure. Examples include creating environments that have physical activity as a norm, reducing the population profile of blood pressure rising with age through better patterns of nutrition, and reducing potential excessive noise exposure.